Academic Libraries as Learning Spaces in Japan: Toward the Development of Learning Commons / Saori Donkai, Atsushi Toshimori and Chieko Mizoue - Donkai, Saori; Toshimori, Atsushi; Mizoue, Chieko (2011)
Since the beginning of the 1990s, new types of learning spaces at academic libraries have emerged mainly in North America. They are called -nformation commons" or -elaming commons." They provide various kinds of services, facilities, and materials in one location to support students' learning. The idea of learning commons has been introduced to colleges and universities in Japan as well. The purpose of this study is to examine the present condition of learning spaces in university libraries in Japan. A questionnaire was sent to 755 main or central libraries at colleges and universities. The response rate was 69.4%. The results of the survey are as follows: (a) simple collaborative learning spaces with desk/desks and chairs have become modestly widespread, while advanced spaces with equipment for information and communication technology, such as computers or projectors, are not common; (b) many libraries provide computer clusters; and (c) cafes and/or beverage vending machines in libraries are still few in number. The survey also reveals that learning commons in Japan is in the early stage of development. Various types of learning spaces are recognized as learning commons. They range from a group learning room with Wi-Fi access to an entire learning commons, where several kinds of facilities, services, and information resources to support students' learning in one location are provided. This diversification may be based on the confusion caused by the rapid introduction of learning commons in Japan. Many learning spaces may rebuild their own services in the near future because of their students' needs.